The Effect Of Breakeltics Exercises On Physical Abilities of First Year Female College Students - Hussein, Marwa; Saed, wasan (Journal of Physical Education, 2019)
The Problem of the research lies in variety and modernity in training through female students acquiring physical fitness that enables them to perform other sports. The aim of the study is to use a modern style to develop the level of fitness in female students. The researchers used the experimental method. The subjects were (30) female students from the college of physical education and sport sciences. The data was collected and treated using proper statistical operations to conclude that Breakletics have a great effect in I’m proving physical fitness in first year college of physical education and sport sciences students/ University Of Baghdad.